Mass Transfer in Back to Back Elbows arranged in an Out of Plane Configuration under Single & Annular Two-Phase Flow Conditions - Le, Thuan (My University, 2013)
Flow-Accelerated Corrosion (FAC) is a pipe wall thinning mechanism affecting carbon steel piping systems in power generation plants. Mass transfer is the rate limiting factor, even though chemistry and materials determine the overall potential for FAC. Different localized thinning rates in back to back elbow configurations between the first and second elbow have been noted at nuclear power plants, and this difference depends on the length of pipe between the elbows, flow conditions, and the configuration of the back to back elbows (e.g. S, C, or out of plane). In this thesis, mass transfer measurements in back to back elbows arranged in an out of plane configuration under single and annular two-phase flow conditions are presented.
The mass transfer measurements were performed using a wall dissolving technique with bend sections cast from gypsum. The diffusivity of gypsum in water is similar to the diffusivity of iron from the magnetite layer of carbon steel pipe in water, thus providing analogous mass transfer conditions to FAC in power generation plants. The wall dissolution of gypsum allows the surface roughness to develop due to the flow. The mass transfer is determined by passing water through the gypsum test sections in a flow loop system. The test sections are then sectioned into two halves to expose the worn surface. The surface topology is measured using a three dimensional laser scanner. The wear progression of the surface with time provides local mass transfer rates, locations of high mass transfer and local surface roughness.
The single-phase flow experiments were performed at a Reynolds number of 70,000 for different lengths of pipe (0, 1, 2 and 5 pipe diameters) between the elbows. The mass transfer results show regions of higher mass transfer in the second elbow in comparison to the first elbow. The maximum mass transfer rate in the second elbow decreases when the length of the pipe between the elbows was increased from 0 to 5 pipe diameters. Surface features corresponding to flow streaks on the second elbow surface indicated swirling flow, and its strength decreases with increasing separation distance between the elbows. The surface roughness was found to be higher in the regions of high mass transfer and decreases with increasing elbow separation distance.
The effect of air and water superficial velocities on the mass transfer for the bends with a separation distance of 0 pipe diameters was measured under two-phase air-water annular flow. In addition, the effect of separation distance of 0, 1 and 5 pipe diameters in length between the elbows was studied for one annular flow condition. The highest mass transfer was found on the outer wall of the first elbow for all cases. The maximum mass transfer in the second elbow was found to be approximately 60 percent of the maximum value in the first elbow, and was not affected significantly when the elbow separation distance was increased from 0 to 1 and 5 pipe diameters. The separation distance between the elbows did not affect the maximum mass transfer on the outer wall of the first elbow. The mass transfer increased with an increase in either the water or air superficial velocity, with the air velocity having a greater effect. The mass transfer enhancement factor relative to that in a straight pipe only increases significantly with increasing air superficial velocity. The roughness development in the pipe was modest, but increases significantly in the high mass transfer region of the first and second elbow.
Keywords: mass transfer; flow accelerated corrosion; out of plane bends; single-phase flow; two-phase flow; piping; Nuclear Engineering; Other Mechanical Engineering; Nuclear Engineering